How does emotional wellbeing relate to underachievement in a general population sample of young adolescents: a neurocognitive perspective - van Batenburg-Eddes, Tamara; Jolles, Jelle (Frontiers in Psychology, 2013)
Abstract Underachievement in school during early adolescence predicts future economic and personal difficulties. Particular neurocognitive skills on the domain of executive functions start to mature during adolescence. This fact and the physical and psychological changes typical for the transition from childhood to adulthood make adolescents vulnerable to emotional problems. The current study investigated the relationship between mild emotional problems which are highly prevalent among adolescents and underachievement in school, and the role of neurocognitive functioning in this relation. This study was conducted in a substantial sample of typical developing young adolescents who just made the transition to secondary education. Pupils were on average 12.5 years old (standard deviation 0.5) , and 45% of the included sample were girls. Emotional wellbeing was associated with underachievement (Odds ratio (OR) 5.15, 95% confidence interval (CI) 3.06-8.68) after adjusting for background variables. Self-reported neurocognitive functioning partly explained the relation between emotional wellbeing and underachievement (OR 2.22, 95% CI 1.23-3.99), yet, emotional wellbeing remained statistically associated with underachievement after correcting for additional confounders (OR 1.99, 95% CI 1.08-3.66). The observed findings suggest that emotional wellbeing plays an essential role in underachievement during the first year of secondary education.